MODERN RECOMMENDATIONS FOR PARENTERAL NUTRITION OF NEWBORN - D.O. Dobryansky; T.K. Znamenska; O.V. Vorobiova (Bukovynian State Medical University, 2020)
The problem of nutritional deficiency and the formation of postnatal body weight deficit in the first days after birth is characteristic mainly of premature babies. Newborns with very low birth weight have energy reserves that meet their needs only during the first 2-3 days of life. Even full-term babies quickly develop a catabolic type of metabolism if they do not get enough protein and calories. All preterm infants have an extremely low birth weight; there is a risk of early postnatal growth retardation associated with the formation of cumulative nutritional deficiencies and negative neurological consequences remotely. Therefore, an important result of quality medical care for newborns is the achievement of adequate (or as adequate as possible) nutrition, prevents or corrects nutritional deficiencies, and ensures the appropriate growth and development of the child. In the absence of full-fledged enteral feeding for medical reasons, parenteral nutrition is used. The purpose of the presented clinical recommendations is to improve the quality of medical care for significantly premature infants (gestational age less than 32 weeks), newborns with necrotizing enterocolitis, surgical pathology of the digestive tract, etc., by introducing modern approaches to effective and safe parenteral nutrition. The data presented are based on the ESPGHAN / ESPEN / ESPR Guidelines on Pediatric Parenteral Nutrition (2018) and NICE Neonatal Parenteral Nutrition (2020) and are intended for neonatologists, pediatric anesthesiologists, pediatricians, nurses, and other healthcare professionals involved in providing medical care to newborns for daily practice